2023
DOI: 10.1111/adj.12960
|View full text |Cite
|
Sign up to set email alerts
|

Positive impacts of oral health services provision by a student‐led primary care clinic to an Australian rural indigenous community

Abstract: BackgroundThis study aimed to determine whether oral health services provision by a dental student clinical outplacement embedded within a Community Controlled Health Service positively impacted a rural Indigenous community and to explore the nature of these benefits.MethodsAggregated and de‐identified 2017, 2018 and 2019 student‐led clinic services provision data were retrospectively analysed. The change in services mix over time was measured. Rural outplacement clinic operational costs to the university were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 19 publications
0
2
0
Order By: Relevance
“…This approach aligns undergraduate curricula with the health needs of rural communities ( 92 ). Furthermore, our study draws parallels with the positive outcomes observed in rural Australia, where a collaborative endeavor between universities and the local community established a student-led clinic service improving access to timely and less invasive care for Indigenous populations ( 93 ). These outcomes underscore the potential for technology-driven solutions to bridge healthcare gaps and optimize the delivery of care to underserved communities, including Indigenous older adults in our study.…”
Section: Discussionmentioning
confidence: 71%
“…This approach aligns undergraduate curricula with the health needs of rural communities ( 92 ). Furthermore, our study draws parallels with the positive outcomes observed in rural Australia, where a collaborative endeavor between universities and the local community established a student-led clinic service improving access to timely and less invasive care for Indigenous populations ( 93 ). These outcomes underscore the potential for technology-driven solutions to bridge healthcare gaps and optimize the delivery of care to underserved communities, including Indigenous older adults in our study.…”
Section: Discussionmentioning
confidence: 71%
“…Gippsland PHN reports an average of 107 medical practitioners per 100 000 people (Gippsland Primary Health Network 2022), compared with the average across Victoria of 120 per 100 000 people (Australian Government Department of Health 2022), with affordable and timely access to GPs identified as a top health issue in the area (Gippsland Primary Health Network 2021b). Student-led healthcare programs offer a sustainable and collaborative alternative health service that can help support underserved populations (March et al 2023), and this study demonstrates the community appreciation of having improved, opportunistic access to simple checks for blood pressure and blood sugar levels, when other services are unavailable.…”
Section: Discussionmentioning
confidence: 80%